Determinan Konsentrasi Spasial dan Daya Saing Industri Manufaktur Besar dan Sedang Jabodetabek - Ilham Muhammad; Zulfa Emalia (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2022)
The aim of this research is to analyze if the large-medium sized manufacture industries in the Jabodetabek are spatially concentrated and to analyze how spatial concentration is affected by the regional and industry specific variabels and the competitiveness strength of said industries. Using Hoover- Balassa Index (HBI) to gauge the spatial concentration strength caused by agglomeration as dependent variable, Industry Size, Competitiveness Index using output-based Location Quotient (LQ), and City/District Minimum Wage (UMK) as independent variables. Using panel data analysis and Geography Information System (GIS) to see where the industries are concentrated spatially in relation to others. It is found that the large and medium-sized manufacture industries in Jabodetabek are indeed spatially concentrated. Granger Causality Test indicates there is only one-way positive causality and that is industry competitiveness to industry spatial concentration. The independent Variable that affect spatial concentration of large and medium-sized industries in Jabodetabek positively are Industry Size, and Competitiveness Index.